The Effectiveness of Health Promotion Strategies for Pregnant Women on Fe Tablet Consumption in the Work Area of Bebesen Health Center, Central Aceh Regency - Sri Wahyuni MS; Barirah Madeni; Hasritawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The distribution coverage of Fe tablets in Bebesen Health Center is still very low, even the lowest compared to other health centers in Central Aceh District, namely 12.40% for Fe1 and 10.56% for Fe3. Failure to achieve the distribution target of Fe tablets in the district can increase the prevalence of anemia. However, there is no clear reporting of anemia in pregnant women, let alone data on adherence to consuming Fe tablets. One of the reasons is the weak monitoring, recording, and reporting system of health workers in consuming Fe tablets and the lack of routine Hb level checks. This study aims to evaluate the effectiveness of health promotion strategies for pregnant women on the consumption of Fe tablets in the Bebesen Health Center Work Area. Methods: Experimental research with participatory action research design (PAR). A sample of 44 pregnant women who were in the Bebesen Health Center area with a gestational age of more than 20 weeks or less than 20 weeks but was the first visit and had made a health visit to a health service place in the working area of the Health Center. Data analysis was carried out with SPSS. Version 25, in the form of univariate and bivariate analysis. Results: The promotional strategy applied was effective in changing the mother's behavior in consuming Fe tablets, Zcount = 5.781 (Zcount > 1.96), and p-value = 0.000 (p<0.05). Conclusion: Provision of effective health promotion strategies on consumption behavior of Fe tablets.